Exchange Market Pressure and Monetary Policy : Asia and Latin America in the 1990s - Tanner, Evan (IMF Working Papers; Working Paper ;, 1999)
Exchange market pressure (EMP), the sum of exchange rate depreciation and reserve outflows (scaled by base money), summarizes the flow excess supply of money in a managed exchange rate regime. Examining Brazil, Chile, Mexico, Indonesia, Korea, and Thailand, this paper finds that monetary policy affects EMP as generally expected: contractionary monetary policy helps reduce EMP. The monetary policy stance is best measured by domestic credit growth (since interest rates contain both policy- and market-determined elements). In response to higher EMP, monetary authorities boosted domestic credit growth both in Mexico (confirming previous research) and in the Asian countries.